Kalimat Efektif dalam Teks Resensi - Melati, Putri; Sudrajat, Yayan (PT. Lancar Media Komunikasi, 2022)
The purpose of this study was to analyze the misuse of effective sentences in the biographical reviewer text of class XII. The research method used to analyze effective sentences in the reviewer text is a qualitative descriptive method with emphasis on content analysis. The technique used by researchers is the analysis of the contents of the reviewer text. After analyzing the characteristics of effective sentences in the text of student reviews, the authors conclude that there are errors in the use of effective sentences in the text of class XII student reviews. After the writer analyzes the reviewer text, finally the writer can conclude the percentage difference as follows: From 21 student reviewer text data, there are 32% of data that has 16 equivalence sentences, 4% of data that has 2 parallelism sentences, 10% of data which has 5 sentences of accuracy , 26% of the data had 13 sentences of efficiency, 14% of the data had 7 sentences of cohesiveness, 2% of the data had 1 sentence of firmness, and there were 12% of the data which had 6 logical sentences. So that the amount of data contained in the table is 50 data.